PELATIHAN TEKNIK COACHING PADA PERAWAT SUPERVISOR DAN APLIKASINYA DI RS X - Christie Lidya Rumerung; Magda Fiske Rumambi; Maria Maxmilla Yoche; Peggy Sara Tahulending (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Nursing is one of the supporting components with the most extensive composition in a hospital, where around 40-60% of health professionals in hospital are nurses. This places nurses as one determining factor in measuring the quality of health services in a hospital. To provide service quality, nurses need to develop themselves by increasing skills, cooperation, and guidance from leader management. Guidance and mentoring are essential to improve nurses' competence and performance. Coaching can be a strategy to achieve management functions through guidance, namely the function of direction and controlling. This PKM aimed to train supervisory nurses to be able to do coaching techniques to nursing staff in their ward. The method includes presentation about coaching materials and coaching session practice (role play). Pre- and post-evaluation were conducted to measure participants’ level of understanding. Workshop was held for partipants to practiced coaching sessions using IGROW technique. Results obtained from eleven participants showed a significant increase in knowledge before and after learning (p=0.003). This PkM recommends the implementation of continuous coaching as well as evaluating the effectiveness of coaching by measuring the level of satisfaction of nursing staff before and after implementation of coaching session.